AKSIOLOGI ILMU PENGETAHUAN - Dhiya Aulia (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This journal discusses in depth the role and contribution of axiology in the development of science in the modern era. Axiology, as a branch of philosophy that studies moral, ethical, and aesthetic values, holds a strategic position in ensuring that scientific progress is not solely oriented toward factual truth and technological innovation, but also pays attention to aspects of social, ecological, and humanitarian benefits. In the context of science, axiology emphasizes the importance of values such as justice, honesty, and responsibility in research processes and the application of scientific innovations, thereby supporting sustainable development and addressing global challenges such as climate change, social inequality, and environmental degradation. Furthermore, this paper highlights the role of axiology in affirming the relationship between theory and praxis, as well as its impact on sustainable and ethical public policymaking. Through a literature analysis of various sources, it is explained that axiology not only helps scientists assess the moral implications of concepts, technologies, or policies, but also strengthens scientific integrity and promotes humanitarian values. Thus, axiology becomes a fundamental foundation for ensuring that science develops responsibly and provides optimal benefits for both present and future generations.